Rapid Determination of Phenolics, Flavonoids, and Antioxidant Properties of Physalis ixocarpa Brot. ex Hornem. and Physalis angulata L. by Infrared Spectroscopy and Partial Least Squares. (4th March 2018) - Cobaleda-Velasco, Marcos; Almaraz-Abarca, Norma; Alanis-Bañuelos, Ruth Elizabeth; Uribe-Soto, José Natividad; González-Valdez, Laura Silvia; Muñoz-Hernández, Gerardo; Zaca-Morán, Orlando; Rojas-López, Marlon
ABSTRACT: Physalis ixocarpa Brot. ex Hornem. and Physalis angulata L. are two edible species of the family Solanaceae, which have an important variety of antioxidant compounds present in their roots, stems, leaves, calyces, and fruits. This work reports the development of multivariate models based on the use of partial least square (PLS) analysis and Fourier transform infrared (FTIR) spectroscopy for the quantitative determination of total phenolics, total flavonoids, free radical scavenging activity, total antioxidant capacity, and reducing power in the extracts of roots, stems, and leaves of both P. ixocarpa and P. angulata . Standard chromatographic and colorimetric techniques were used to determine the quantitative actual values (references) in the extracts, which served as input data to develop the multivariate PLS models. Optimized FTIR-PLS models were realized by cross-validation procedures, obtaining the determination coefficients for prediction between 0.792 and 0.905 for P. ixocarpa, and between 0.756 and 0.893 for P. angulata . In this form, FTIR spectroscopy with multivariate analysis could represent a versatile tool to evaluate quantitatively concentrations of bioactive compounds and antioxidant properties in the extracts of both species, requiring a very short time at low cost.